2021
DOI: 10.1111/jdv.17304
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of bullous pemphigoid with neuropsychiatric comorbidities is associated with anti‐BP230 seropositivity

Abstract: Background While clustering of bullous pemphigoid (BP) with neuropsychiatric diseases is well‐established, the clinical and immunological profile of BP patients with this comorbidity remains to be decisively determined. Objectives To evaluate the burden of neurological and psychiatric comorbidities among patients with BP and to elucidate the clinical, immunological and immunopathological features of patients with BP and comorbid neuropsychiatric conditions. Methods We performed a retrospective study encompassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
13
0
3
Order By: Relevance
“…Bullous pemphigoid230 subtypes, including BPAG1a1 and BPAG1a2, were expressed in both peripheral and central nervous systems. Seropositivity of BP230 was found to be a predictor of neuropsychiatric comorbid diseases in patients with BP [33]. With respect to BP180, apart from the skin tissue, the presence of type XVII collagen was also found in human cortical, hippocampal, and amygdaloid neurons [34].…”
Section: Discussionmentioning
confidence: 99%
“…Bullous pemphigoid230 subtypes, including BPAG1a1 and BPAG1a2, were expressed in both peripheral and central nervous systems. Seropositivity of BP230 was found to be a predictor of neuropsychiatric comorbid diseases in patients with BP [33]. With respect to BP180, apart from the skin tissue, the presence of type XVII collagen was also found in human cortical, hippocampal, and amygdaloid neurons [34].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, high serum anti‐BP180 IgG levels at the time of diagnosis were indicative for an early death and a higher number of infections 41–44 . In contrast, lower serum anti‐BP180 IgG levels were described in DPP4 inhibitor‐associated BP, 45,46 whereas BP230 reactivity was linked with neuropsychiatric comorbidities 47 …”
Section: Discussionmentioning
confidence: 97%
“…[41][42][43][44] In contrast, lower serum anti-BP180 IgG levels were described in DPP4 inhibitor-associated BP, 45,46 whereas BP230 reactivity was linked with neuropsychiatric comorbidities. 47 The aim of the present study was to explore the association of autoantibody reactivities with comorbidities and the medication of BP patients in a large multicentric cohort. Therefore, data on comorbidities and concomitant medication were collected prospectively in a large cohort of patients diagnosed on wellestablished criteria in 16 dermatological referral centers for autoimmune blistering diseases from six European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Using multivariate analysis, a large retrospective study of 273 BP patients showed that the presence of anti-BP230 antibodies, in addition to other variables, such as older age and female sex, was associated with the coexistence of neuropsychiatric disorders. After adjusting for confounders, anti-BP230 seropositivity proved to be the only independently significant predictor for comorbidity of neuropsychiatric diseases, such as dementia, epilepsy, multiple sclerosis, depression, and bipolar disorder in BP patients [ 64 ]. In another smaller study, BP patients with a comorbid neurological disease were found to have higher levels of both BP180 and BP230 autoantibodies, with a higher seropositivity rate for BP230 [ 65 ].…”
Section: Significance Of Bp230 To Neurological Disorders and Bpmentioning
confidence: 99%